2020
DOI: 10.1016/j.clnesp.2020.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of bioelectrical impedance analysis to monitor changes in fat-free mass during recovery from colorectal cancer– a validation study

Abstract: Background & aims: Although previous research show high correlation between fat-free mass (FFM) measured by bioelectrical impedance analysis (BIA) and dual-energy X-ray absorptiometry (DXA), the validity of BIA to track longitudinal changes in FFM is uncertain. Thus, the aim of this study was to validate the ability of BIA to assess changes in FFM during 6 months of recovery from non-metastatic colorectal cancer (CRC). Methods: A total of 136 women and men (50e80 years) with stage I-III CRC and a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The authors reported that more studies are needed to validate BIA in tracking changes in lean body mass. 31 In a study that validated BIA in the evaluation of body composition of patients with colorectal cancer, it was reported that BIA is a valuable tool for identifying low fat-free body mass as part of the diagnosis of malnutrition of BIA. 32 One validation study was conducted in a small sample (n = 17) of patients with chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that more studies are needed to validate BIA in tracking changes in lean body mass. 31 In a study that validated BIA in the evaluation of body composition of patients with colorectal cancer, it was reported that BIA is a valuable tool for identifying low fat-free body mass as part of the diagnosis of malnutrition of BIA. 32 One validation study was conducted in a small sample (n = 17) of patients with chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that monitored longitudinal change in FFM in patients with colorectal cancer and validated BIA, it was reported that when compared with DXA, BIA overcalculated FFM for both loss and gain but showed 100% sensitivity and 90% specificity in FFM losses which were >5%. The authors reported that more studies are needed to validate BIA in tracking changes in lean body mass 31 . In a study that validated BIA in the evaluation of body composition of patients with colorectal cancer, it was reported that BIA is a valuable tool for identifying low fat‐free body mass as part of the diagnosis of malnutrition of BIA 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Their study concluded that FFM estimated from both BIA devices exhibited good agreement with DXA, as long as the appropriate equation was used [40]. However, Bärebring et al [71] reached contrasting conclusions in their study, which aimed to validate the ability of BIA, compared to DXA, to assess changes in FFM in non-metastatic CRC patients. BIA yielded imprecise data on changes in FFM, regardless of the equation used, and was therefore not deemed a valid option for quantifying changes in FFM in patients with CRC.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Gupta et al conducted two separate studies investigating the prognostic role of PhA in advanced CRC [23] and the association between BIA-derived PhA and Subjective Global Assessment (SGA) [72]. The findings from both studies recognized BIA-derived PhA as a prognostic and potential nutritional indicator in advanced CRC patients [23,31,[34][35][36][37]40,41,71,72].…”
Section: Colorectal Cancermentioning
confidence: 99%